(untitled) (MAUSAM, 1996)
A linear model of the steady response of a stratified fluid to isolated heat sources is used to study the maintainence of the mean position of the mid-tropospheric ridge and its displacemerit. It is well known that the performance of the southwest Indian monsoon is intimately related to the latitudinal position of the April 500 hPa ridge along 75°E. Recent observational studies have demonstrated that the winter/spring snow cover over Eurasia are negatively related to the April 500 hPa ridge position. In this study we propose one possible physical mechanism of southward displacement of the mid-tropospheric ridge. The anomalous cooling associated with the increased snow cover in Eurasia may be considered as a heat sink north of the tropical heal sources. It is demonstrated that such a heat sink can result in significant southward displacement of the mid-tropospheric ridge.